Structure and Biosynthesis of Crocagins: Polycyclic Posttranslationally Modified Ribosomal Peptides from Chondromyces crocatus. Issue 26 (23rd May 2017) - Viehrig, Konrad; Surup, Frank; Volz, Carsten; Herrmann, Jennifer; Abou Fayad, Antoine; Adam, Sebastian; Köhnke, Jesko; Trauner, Dirk; Müller, Rolf
Abstract: Secondary metabolome mining efforts in the myxobacterial multiproducer of natural products, Chondromyces crocatus Cm c5, resulted in the isolation and structure elucidation of crocagins, which are novel polycyclic peptides containing a tetrahydropyrrolo[2, 3‐b]indole core. The gene cluster was identified through an approach combining genome analysis, targeted gene inactivation in the producer, and in vitro experiments. Based on our findings, we developed a biosynthetic scheme for crocagin biosynthesis. These natural products are formed from the three C‐terminal amino acids of a precursor peptide and thus belong to a novel class of ribosomally synthesized and post‐translationally modified peptides (RiPPs). We demonstrate that crocagin A binds to the carbon storage regulator protein CsrA, thereby inhibiting the ability of CsrA to bind to its cognate RNA target. Abstract : Ribosomally synthesized and posttranslationally modified peptides (RiPPs) were isolated from a myxobacterial producer. The unusual tetracyclic peptide scaffold of these crocagins turned out to originate from a ribosomally assembled precursor peptide. Isolation, structure elucidation, mutagenesis of the producer, and in vitro experiments are presented.